2(x+12)=23

Simple and best practice solution for 2(x+12)=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+12)=23 equation:



2(x+12)=23
We move all terms to the left:
2(x+12)-(23)=0
We multiply parentheses
2x+24-23=0
We add all the numbers together, and all the variables
2x+1=0
We move all terms containing x to the left, all other terms to the right
2x=-1
x=-1/2
x=-1/2

See similar equations:

| (3x-30°=) | | 20-3f=-5 | | 4x2+14x−30=0 | | 6x^3-31x^2+3x+10=0/ | | 2(6.3-2.2x)=x-3.6 | | 6a+4=1/3 | | 4+-5x=34 | | n-71=171 | | 32=–6x–2x | | 9r=-6r^2-3 | | –38d+5d+–4d+40d−–33=–36 | | 2/3×d=10/9/ | | -6=-3w^2-8w | | 7v^2-7v+7=0 | | x5+9=15 | | V^2-5v+8=0 | | 9=-t^2-6t | | -41=h/6+30 | | 2a+1=-9a^2 | | 9(2n+4)=7(7n+7)+2 | | 3/x+3=5 | | -3=-v^2+9v | | 23· n = 512 | | h​/15−17=−13 | | 9r^2-5r=0 | | -5f-12=18 | | 7=d+29/7 | | 4a^2-6=0 | | 0.10(68-y)+0.5y=6.00 | | Y=300+450x | | 7+x-4x=-17 | | u/2-1=9 |

Equations solver categories